Hubungan Tingkat Pengetahuan Gizi Dan Pola Makan Dengan Kejadian Obesitas Pada Siswa Smk Negeri 1 Biaro - Jufri Sineke; Mirna Kawulusan; Rudolf B. Purba; Anita Dolang (Jurnal GIZIDO, 2019)
Obesity is a problem worldwide because of its increasing prevalence in adults and adolescents. Riskesdas results showed an increase in the prevalence of over nutrition in children aged 16-18 years, for the fat category from 1.4% in 2010 to 7.3% consisting of 5.7% fat and 1.6% obesity in 2013. This study aims to determine the relationship between the level of nutritional knowledge and eating patterns with the incidence of obesity in students of Biaro 1 Vocational School. This research is an analytic observational descriptive study with cross sectional design, with a sample of 36 people who met the inclusion criteria. Data was collected through interviews using nutritional knowledge questionnaires and semi-FFQ forms to determine dietary patterns, and measurements of abdominal circumference for obesity data. Univariate analysis was performed descriptively and the bivariate analysis used was the correlation test with Kendall's tau-b with a value of α = 0.05. The results of this study showed that the level of nutritional knowledge of 36 respondents was mostly lacking at 50.0%, the respondents' eating patterns were mostly not good at 80.6%, and obesity status with an average abdominal circumference size of 80-85 cm was 55.7%. Statistical test results show that there is a relationship between the level of nutritional knowledge and eating patterns with the incidence of obesity in students of State Vocational School 1 Biaro (p <0.05).